please answer me these three questions. I will mark you as brainliest....
Attachments:
![](https://hi-static.z-dn.net/files/de0/0c6e58b0666c30131ba1d63f38382a18.jpg)
Answers
Answered by
1
7. The first one is easy you just need to convert it from mix fraction to fraction.
5×3+4/5=19/5
Dividing 19 by 5 we get: 3.8 (in decimal form)a
8.
![a = 1 + \sqrt{7} a = 1 + \sqrt{7}](https://tex.z-dn.net/?f=a+%3D+1+%2B+%5Csqrt%7B7%7D+)
Then we need to find the value of -6/a. So all we need to do is place the value of a.
Placing value of a we get:
![- 6 \div 1 + \sqrt{7} \\ - 6 \div 1 + \sqrt{7} \\](https://tex.z-dn.net/?f=+-+6+%5Cdiv+1+%2B+%5Csqrt%7B7%7D+%5C%5C+)
NOW here the tricky part comes. This process is called rationalisation.
So the answer comes out to be 1-root7
9. In this question you just need to place the values given:
f(x)=5x^2-4x+5
f(1)=5(1)^2-4×1+5=6
f(-1)=5(-1)^2-4×(-1)+5=14
f(0)=5(0)^2-4×0+5=5
Therefore,
f(1)+f(2)+f(0)=6+14+5=25
5×3+4/5=19/5
Dividing 19 by 5 we get: 3.8 (in decimal form)a
8.
Then we need to find the value of -6/a. So all we need to do is place the value of a.
Placing value of a we get:
NOW here the tricky part comes. This process is called rationalisation.
So the answer comes out to be 1-root7
9. In this question you just need to place the values given:
f(x)=5x^2-4x+5
f(1)=5(1)^2-4×1+5=6
f(-1)=5(-1)^2-4×(-1)+5=14
f(0)=5(0)^2-4×0+5=5
Therefore,
f(1)+f(2)+f(0)=6+14+5=25
Attachments:
![](https://hi-static.z-dn.net/files/d72/a8f7934e350ce2d21cf7f67d1da03433.jpg)
drashucute99:
thank you so so much
Similar questions